Congress - Quiri, Patricia Ryon (New York Children's Press, 1998)
Describes the origins, functions, and duties of the United States Congress. Includes an explanation of how to write a letter to a member of Congress
American Corner
Includes bibliographical references (p. 44) and index
11
Keywords: United States -- Congress -- Juvenile literature; United States -- Congress